RESEARCH OF THE MULTIPATH TRAFFIC ROUTING METHOD IN THE INTERNET OF THINGS NETWORK - Chumachenko, Serhii; Chumachenko, Bohdan; Maloied, Maryna; Odarchenko, Roman; Burmak, Yuliia (Science-based technologies, 2025)
Load balancing is the process of redistributing network traffic between several channels in order to reduce the load on congested communication lines. This is achieved through the use of multipath routing protocols, which have the ability to redirect data along alternative paths, which contributes to more efficient delivery of information. When forming a group of routes with different technical characteristics, traffic distribution plays a key role. Incorrect distribution of traffic can lead to a decrease in the equivalent data transfer rate. Therefore, a methodology is needed that takes into account both the selection of the optimal set of routes and the determination of traffic distribution coefficients on each of them. The proposed method is based on the principles of dynamic programming for the optimal selection of a subset of routes and determination of the values ​​of traffic distribution coefficients, which ensures their consistency with the network. The results of the simulation show that the proposed strategy can significantly increase the efficiency of using network resources. Compared to random selection of routes and uniform distribution of traffic, the data transfer rate increases by an average of 40%.